PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA CAFE SEDUH DI BESUKI DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING - Putri, Dwi Maryamah Haniza; Soeliha, Siti; Sari, Rini Kartika (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Cafe is one of the places to relax and chat where visitors can order drinks and food. Cafe has quite a lot of potential in helping the economy in a region. The purpose of this study is to analyze the Influence of Product Quality, Price, and Promotion on Purchasing Decisions with Purchase Interest as an intervening variable. The population in this study were consumers of Cafe Seduh in Besuki. The sampling technique was determined by simple random sampling. Data analysis and hypothesis testing in this study used the Structural Equation ModelPartial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Product Quality has a positive but insignificant effect on Purchase Interest, Price has a negative but insignificant effect on Purchase Interest, Promotion has a significant positive effect on Purchase Interest, Product Quality has a positive but insignificant effect on Purchase Decision, Price has a significant positive effect on Purchase Decision, Promotion has a significant positive effect on Purchase Decision, Purchase Interest has a negative but insignificant effect on Purchase Decision, Product Quality has a negative but insignificant effect on Purchase Decision through Purchase Interest, Price has a significant positive effect on Purchase Decision through Purchase Interest, Promotion has a negative but insignificant effect on Purchase Decision through Purchase Interest.